2012
DOI: 10.4081/ijas.2012.e9
|View full text |Cite
|
Sign up to set email alerts
|

Wild red deer[Cervus elaphusL.) grazing may seriously reduce forage production in mountain meadows

Abstract: This study aimed at estimating the impact of red deer grazing on the productivity of meadows located in Pian Cansiglio, north-eastern Italian Pre-Alps. These meadows (185 ha; average elevation 1000 m asl are managed for hay/silage production (1-2 cuts per season) and are included in a protected area that hosts a high density of deer (around 30 heads/100 ha). In 2008 and 2010, dry matter (DM) production and loss due to deer grazing were estimated with exclusion cages (1 m 2 ; 48 exclusion cages in 2008 and 52 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…This is especially true both in the main valleys, where the alternatives are arable crops or (in the Trento Province) wine and fruit crops, characterized by a very low biodiversity value (Zimmermann et al, 2010), and in the steeper areas of the valleys slopes, where the alternative is afforestation (Cocca et al, 2012;Marini et al, 2009). Moreover, "Traditional" dairy systems (mainly the "Original Traditional") contribute to offfarm biodiversity, mainly because they maintain an environment more suitable to wildlife (Giupponi et al, 2006;Ramanzin et al, 2009), even though the traditional farms may suffer food competition between domestic and wild animals (Cocca et al, 2007;Marchiori et al, 2012).…”
Section: Land Usementioning
confidence: 98%
“…This is especially true both in the main valleys, where the alternatives are arable crops or (in the Trento Province) wine and fruit crops, characterized by a very low biodiversity value (Zimmermann et al, 2010), and in the steeper areas of the valleys slopes, where the alternative is afforestation (Cocca et al, 2012;Marini et al, 2009). Moreover, "Traditional" dairy systems (mainly the "Original Traditional") contribute to offfarm biodiversity, mainly because they maintain an environment more suitable to wildlife (Giupponi et al, 2006;Ramanzin et al, 2009), even though the traditional farms may suffer food competition between domestic and wild animals (Cocca et al, 2007;Marchiori et al, 2012).…”
Section: Land Usementioning
confidence: 98%
“…In the US Yellowstone National Park, forage removal by red deer and bison accounted for 22% to 58% of the ANPP (Frank & McNaughton, 1992). In a protected area in the Italian Pre-Alps, wild red deer consumed high amounts of biomass in agriculturally used mountain meadows, reaching up to 40% of the biomass at the second cut (Marchiori, Sturaro, & Ramanzin, 2012), and in south-eastern Slovenia, red deer grazing in grasslands close to forest borders reduced the herbage yield by 50% on average (Trdan & Vidrih, 2007).…”
Section: Anpp and Forage Removal By Red Deer In Grasslandsmentioning
confidence: 99%
“…Study by Marchiori et al (2012) confirmed that high densities of red deer seriously impact on forage production by mountain meadows. But these studies are not very well comparable, because their study aimed at estimating the impact of red deer grazing on the productivity of meadows located in Pian Cansiglio.…”
Section: Discussionmentioning
confidence: 69%
“…But these studies are not very well comparable, because their study aimed at estimating the impact of red deer grazing on the productivity of meadows located in Pian Cansiglio. Marchiori et al (2012) specify that the study concentrated on the damages to meadows, but it is also important to stress that this problem must be addressed with an ecosystem and holistic approach.…”
Section: Discussionmentioning
confidence: 99%